Academic feminism in Mexico. Emergence and current challenges (GAMU women) - Morales Bautista, María Luisa (2025)
The objective of this study is to make visible and analyze the personal, academic and institutional experience of academic women from Mexico, pioneers of the academic feminist movement, promoters and participants of the first Autonomous Group of University Women GAMU and the first Center for Women’s Studies CEM through of interviews and their narrative analysis. The results show the main achievements of GAMU and CEM: the generation of seminars, writings and collection of texts on topics related to violence against women, the beginning of complaints against harassing academics, the first march against violence in the university, as well as the fight for women’s rights inside and outside the classrooms.